Soluble RANKL contributes to osteoclast formation in adult mice but not ovariectomy-induced bone loss - Jinhu Xiong (Nature Portfolio, 2018)
RANKL is a cytokine produced as a membrane-bound and a secreted protein. Here, using mice lacking soluble RANKL, the authors show that the secreted protein is important for osteoclast function, but not for mammary gland and lymphocyte development.